2010
DOI: 10.1007/s10661-010-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin levels and incidence of mould in Turkish rice

Abstract: One hundred unpackaged rice samples, each weighing 500 g, were randomly collected at retail stores and open markets in the largest rice growing area (Thrace) in Turkey and analysed for mould counts, predominant mould genera, moisture content and mycotoxin levels. Mould counts ranged from 1.0 × 10(1) to 1.5 × 10(4) cfu/g in 70 of 100 samples, and the correlation between moisture content and mould count was significant (p ≤ 0.05). Aspergillus spp. and Penicillium spp., potential mycotoxin producers, were the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 26 publications
(36 reference statements)
4
46
1
4
Order By: Relevance
“…In Iran, 182 rice samples were analysed by HPLC-FLD; and OTA was detected in 6% of rice samples, with a mean value of 1.6 ng/g in positive samples (range, 0.2-4.8 ng/g) (Feizy et al 2011). In another study from Turkey, OTA levels in unpackaged rice samples were found by ELISA to be higher than the legal limits of the EC regulation in 30% of rice samples; the highest OTA level was 80.7 ng/g in one sample (Aydin et al 2011). …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In Iran, 182 rice samples were analysed by HPLC-FLD; and OTA was detected in 6% of rice samples, with a mean value of 1.6 ng/g in positive samples (range, 0.2-4.8 ng/g) (Feizy et al 2011). In another study from Turkey, OTA levels in unpackaged rice samples were found by ELISA to be higher than the legal limits of the EC regulation in 30% of rice samples; the highest OTA level was 80.7 ng/g in one sample (Aydin et al 2011). …”
Section: Resultsmentioning
confidence: 91%
“…fumonisin (Makun et al 2011;Ortiz et al 2013;Rofiat et al 2015), aflatoxins (Nguyen et al 2007;Rahmani et al 2010;Aydin et al 2011;Makun et al 2011;Ortiz et al 2013;Lai et al 2014b;Rofiat et al 2015), but also beauvericin (Nazari et al 2015;Rofiat et al 2015), citrinin (Nguyen et al 2007;Rofiat et al 2015), patulin (Makun et al 2011), sterigmatocystin, moniliformin, fumonisin B 3 , cytochalasins (Rofiat et al 2015), enniatins (Nazari et al 2015), zearalenone (Rahmani et al 2010;Makun et al 2011;Lee et al 2015), deoxynivalenol (Dors et al 2011;Makun et al 2011;Ortiz et al 2013), and ochratoxin A (Pena et al 2005;Ghalia et al 2008;Juan et al, 2008;Frelund et al 2009;Buyukunal et al 2010;Rahmani et al 2010;Aydin et al 2011;Bansal et al 2011;Almeidaa et al 2012;Mosayebi & Mirzaee 2014;Rahimi 2014;Venkataramana et al 2015;Xianwen et al 2015). The rice parboiling process increases the migration of mineral salts by about 30% into parboiled rice (compared to white rice) during the soaking and boiling steps (Dors et al 2009).…”
mentioning
confidence: 99%
“…O limite máximo de aflatoxinas no arroz, estabelecido pelo Turkish Food Codex (TFC) (AYDIN et al, 2011), é de 4 μg/kg. Um estudo realizado por Aydin et al (2011) revelou que 56% das 100 amostras de arroz produzido na Turquia estavam contaminadas com aflatoxinas, num intervalo de 0,05 μg/kg a 21,4 μg/kg, sendo que 32% estavam acima do limite máximo estabelecido pelo TFC.…”
Section: Fungos Produtores De Aflatoxinasunclassified
“…As micotoxinas que já foram encontradas nas amostras de arroz são: citrinina, luteosquirina, cicloclorotina, islanditoxina, rugulosina, ocratoxina A, aflatoxinas, desoxinivalenol, fumonisinas e zearalenona, entre outras (FREDLUND et al, 2009;AYDIN et al, 2011;ALMEIDA et al, 2012). Na presente revisão, serão tratados os aspectos gerais do arroz, sua produção, ocorrência de fungos, aflatoxinas e micotoxinas no Brasil e no mundo, bem como a redução de aflatoxinas durante o processamento do arroz.…”
Section: Introductionunclassified
“…The fungal and aflatoxins contamination was reported in rice in Turkey (Aydin et al, 2010); in maize from south-western Nigeria (Bankole & Mabekoje, 2004), Brazil (Rocha et al, 2009) and northern Italy (Pietri et al, 2004); in domestic and imported beers in Canada (Mably et al, 2005); and in peanuts in the Cote d'Ivoire (Sangare-Tigori et al, 2006), between others. Since contamination of grains with mycotoxins is not efficiently eliminated by most of the food processing operations such as sorting, trimming, cleaning, milling, brewing, cooking, baking, frying, roasting, canning, flaking, alkaline cooking, nixtamalization, and extrusion; the fungal toxins are commonly found in grain by-products.…”
Section: Approaches In the Articles Regarding To Foodsmentioning
confidence: 99%